Doxorubicin-loaded bacterial outer-membrane vesicles exert enhanced anti-tumor efficacy in non-small-cell lung cancer - Kudelaidi Kuerban; Xiwen Gao; Hui Zhang; Jiayang Liu; Mengxue Dong; Lina Wu; Ruihong Ye; Meiqing Feng; Li Ye (Elsevier, 2020)
More efficient drug delivery system and formulation with less adverse effects are needed for the clinical application of broad-spectrum antineoplastic agent doxorubicin (DOX). Here we obtained outer-membrane vesicles (OMVs), a nano-sized proteoliposomes naturally released by Gram-negative bacteria, from attenuated Klebsiella pneumonia and prepared doxorubicin-loaded O0MVs (DOX-OMV). Confocal microscopy and in vivo distribution study observed that DOX encapsulated in OMVs was efficiently transported into NSCLC A549 cells. DOX-OMV resulted in intensive cytotoxic effects and cell apoptosis in vitro as evident from MTT assay, Western blotting and flow cytometry due to the rapid cellular uptake of DOX. In A549 tumor-bearing BALB/c nude mice, DOX-OMV presented a substantial tumor growth inhibition with favorable tolerability and pharmacokinetic profile, and TUNEL assay and H&E staining displayed extensive apoptotic cells and necrosis in tumor tissues. More importantly, OMVs' appropriate immunogenicity enabled the recruitment of macrophages in tumor microenvironment which might synergize with their cargo DOX in vivo. Our results suggest that OMVs can not only function as biological nanocarriers for chemotherapeutic agents but also elicit suitable immune responses, thus having a great potential for the tumor chemoimmunotherapy.